2020
DOI: 10.1073/pnas.2001966117
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 receptor polymorphisms regulate T cells and T cell-dependent inflammatory diseases

Abstract: It has proven difficult to identify the underlying genes in complex autoimmune diseases. Here, we use forward genetics to identify polymorphisms in the vitamin D receptor gene (Vdr) promoter, controlling Vdr expression and T cell activation. We isolated these polymorphisms in a congenic mouse line, allowing us to study the immunomodulatory properties of VDR in a physiological context. Congenic mice overexpressed VDR selectively in T cells, and thus did not suffer from calcemic effects. VDR overexpression resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Vitamin D modulates immune responses. Its receptors are expressed on nearly all immune cells, primarily CD8 and CD4 T lymphocytes ( 45 ). In addition to responding to infection, it also prevents the development of autoimmune diseases, such as type 1 diabetes, systemic lupus erythematosus, and inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D modulates immune responses. Its receptors are expressed on nearly all immune cells, primarily CD8 and CD4 T lymphocytes ( 45 ). In addition to responding to infection, it also prevents the development of autoimmune diseases, such as type 1 diabetes, systemic lupus erythematosus, and inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…P4HB catalyzes the formation of 4-hydroxyproline in collagen [ 49 ] while PDIA3 interacts with calcitriol, an active form of vitamin D3, which could regulate gene expression through binding to the nuclear receptor vitamin D receptor (VDR) in cells [ 50 ]. Interestingly, genetic polymorphism of the VDR promoter, which controls VDR expression and T cell activation, is associated with the development of CIA [ 51 ]. Moreover, we could also show that the oxidized P4HB and PDIA3 protein levels were enhanced in day 7 CIA splenocytes from NCF4 [58A] mice.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was observed that deficiency of vitamin D3 is associated with increased autoimmunity and enhanced susceptibility to infection ( Aranow, 2011 , Martens et al, 2020 ). Moreover, it was also revealed that vitamin D3 supplements result in elevated T cell levels along with their enhanced activity ( Fernandez Lahore et al, 2020 ). All the preceding discussion makes vitamin D3 an attractive drug to manage COVID-19 disease.…”
Section: Therapeutic Approaches For the Treatment Of Coronavirus Dise...mentioning
confidence: 99%